Effect of plant fibers on the physical properties of slurry-processed reconstituted tobacco - Liu, Tong; Wang, Yixuan; Wang, Chunping; Zhang, Qi; Wang, Le; Li, Yuhan; Xu, Linyang; Jin, Xinyan; Yin, Xianzhong; Zhang, Zhan; Luo, Chong; Fu, Lili; et al. (Frontiers in Chemistry, 2024)
The primary function of plant fibers in reconstituted tobacco is to enhance the physical strength, and it can quite modify their physical properties. This study demonstrated the effect of various plant fibers and their beating degrees on the physical properties of reconstituted tobacco. Tensile index, burst index, uniformity, tensile stiffness orientation, and thermal conductivity coefficient were examined. The result revealed that the mechanical properties of reconstituted tobacco varied according to the type and beating degree of the fibers. The mechanical properties of softwood, cotton, and bast fibers showed an initial increase followed by a decrease with increasing beating degree, while bamboo fiber showed a continuous improvement in mechanical properties proportional to the beating degree. Conversely, hardwood fiber displayed an inverse relationship with its beating degree. Under identical beating conditions, reconstituted tobacco containing softwood fibers showed the greatest improvement in tensile properties, achieving the highest tensile strength, thermal conductivity, and specific heat capacity. In particular, when softwood fibers were beaten to 50 °SR, the physical properties of the reconstituted tobacco peaked, with longitudinal and transverse tensile indices improving by 42.48% and 12.11%, respectively. Additionally, the bursting resistance index increased by 61.93%, and the thermal conductivity coefficient increased by 5.94%.